Webinar series 3/2021 – a global perspective on online learning / Sharifah Sheha Syed Aziz Baftim - Syed Aziz Baftim, Sharifah Sheha (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
The third webinar organized by Universiti Teknologi MARA Negeri Sembilan, Kampus Kuala Pilah titled “A Global Perspective on Online Learning” was held on Wednesday, 16th June 2021, involving students from two universities as guest speakers. Representing Universiti Teknologi MARA Negeri Sembilan, Kampus Kuala Pilah as guest speakers were Nurul Allia Binti Abdul Malik (Degree in Science & Food Technology) and Nur Tasnin Athirah Binti Faizul (Diploma in Textile Technology) with Sofea Jasmine Binti Mohd Zahiruddin (Diploma in Microbiology) as a reserved guest speaker. Two guest speakers from Universitas Pahlawan Tuanku Tambusai were invited, namely Selvi Oktafia (Degree in Nursing) and Aziza Oktavia (Degree in English as a Second Language). The one- hour webinar was held through the use of Cisco Webex and APB Kuala Pilah YouTube channel with Ms Siti Nur Dina Mohd Ali as the Moderator and Ms Fatin Nabila Abdul Razak as the Master of Ceremony.